Apurinic/Apyrimidinic Endonucleases of Mycobacterium tuberculosis Protect against DNA Damage but Are Dispensable for the Growth of the Pathogen in Guinea Pigs - Puri, Rupangi Verma (Public Library of Science, 2014)
In host cells, Mycobacterium tuberculosis encounters an array of reactive molecules capable of damaging its genome. Non-bulky DNA lesions are the most common damages produced on the exposure of the pathogen to reactive species and base excision repair (BER) pathway is involved in the repair of such damage. During BER, apurinic/apyrimidinic (AP) endonuclease enzymes repair the abasic sites that are generated after spontaneous DNA base loss or by the action of DNA glycosylases, which if left unrepaired lead to inhibition of replication and transcription. However, the role of AP endonucleases in imparting protection against DNA damage and in the growth and pathogenesis of M.tuberculosis has not yet been elucidated. To demonstrate the biological significance of these enzymes in M.tuberculosis, it would be desirable to disrupt the relevant genes and evaluate the resulting mutants for their ability to grow in the host and cause disease. In this study, we have generated M.tuberculosis mutants of the base excision repair (BER) system, disrupted in either one (MtbΔend or MtbΔxthA) or both the AP endonucleases (MtbΔendΔxthA). We demonstrate that these genes are crucial for bacteria to withstand alkylation and oxidative stress in vitro. In addition, the mutant disrupted in both the AP endonucleases (MtbΔendΔxthA) exhibited a significant reduction in its ability to survive inside human macrophages. However, infection of guinea pigs with either MtbΔend or MtbΔxthA or MtbΔendΔxthA resulted in the similar bacillary load and pathological damage in the organs as observed in the case of infection with wild-type M.tuberculosis. The implications of these observations are discussed.